Relapse rate and long-term management of plaque psoriasis after treatment with photochemotherapy and dithranol. Issue 6268 (21st March 1981) - Vella Briffa, D; Greaves, M W; Warin, A P; Rogers, S; Marks, J; Shuster, S
Abstract : The relapse rate of plaque psoriasis after initial clearing with the "Ingram" dithranol regimen or photochemotherapy was comparable when no maintenance treatment was given. It was estimated that psoriasis recurs to half of its pretreatment extent after about six months in half the patients. Maintenance treatment with photochemotherapy once a week or once every three weeks was useful in reducing the relapse rate. This study failed to show any statistical difference in relapse rates between these two maintenance schedules. If this finding turns out to be true over longer periods of study the maintenance schedule entailing treatment once every three weeks with its lower cumulative dose of long-wave ultraviolet light will clearly be preferable. The psoriasis in most patients was under better overall control with maintenance treatment than with intermittant clearing courses given when the extent of the psoriasis had become unacceptable to them. There was, however, a group of roughly one-fifth of patients who remained in satisfactory remission for over 16 months after initial clearing. Regular maintenance treatment was unnecessary in them. Much more information is needed on response to treatment in subgroups of patients to permit recognition from the start of which patients are likely to have long remission and which are not.